Relationships between surrogate measures of mechanical and psychophysiological load, patellar tendon adaptations, and neuromuscular performance in NCAA division I men's volleyball athletes - Guthrie, Brian M.; King, Erica L.; Patwardhan, Shriniwas; Wei, Qi; Sikdar, Siddhartha; Chitnis, Parag V.; Jones, Margaret T. (Frontiers in Sports and Active Living, 2023)
The aim of the current study was to examine intra-individual associations between workloads and patellar tendon properties and neuromuscular performance in collegiate volleyball athletes. Participants included National Collegiate Athletics Association Division I men’s volleyball athletes (n=16, age: 20.33 ± 1.15 yrs, height: 193.50 ± 6.50 cm, body mass: 84.32 ± 7.99 kg, bodyfat%: 13.18 ± 4.72 %) competing across 9 weeks of in-season competition. Daily measurements of external workloads (i.e., jump count) and internal workloads (i.e., session rating of perceived exertion (sRPE)) were recorded. Weekly measurements included neuromuscular performance assessments (i.e., countermovement jump, drop jump), and ultrasound images of the patellar tendon to evaluate structural adaptations. Repeated measures correlations assessed intra-individual associations among performance and patellar tendon metrics. Peak force of the countermovement jump exhibited small (r-rm = -0.26, p = 0.02) and moderate (r-rm = -0.31, p = 0.03) negative associations with jump count and workload efficiency of the previous week, respectively. Drop jump height exhibited a moderate negative association (r-rm = -0.30, p = 0.03) with jump count of the previous week. Echogenicity of the dominant limb exhibited small (r-rm = 0.24, p = 0.03) and moderate (r-rm = 0.32, p = 0.003) positive associations with sRPE of the previous week and jump count of the previous week, respectively. Thickness of the dominant limb exhibited a small negative association (r-rm = -0.24, p = 0.03) with jump count of the previous week. Echogenicity of the non-dominant limb exhibited small (r-rm = -0.23, p = 0.01) and moderate (r-rm = -0.30, p = 0.001) negative associations with jump count and sRPE, respectively. Thickness of the non-dominant limb exhibited a small positive association (r-rm = 0.20, p = 0.03) with workload efficiency. Stiffness of the non-dominant limb exhibited a small negative association (r-rm = -0.21, p = 0.04) with jump count of the previous week. These results contribute to the existing literature in workload monitoring of collegiate men’s volleyball athletes by addressing associated changes in neuromuscular performance and patellar tendon structure across a sport season.